An estimation of residual lifetime of spatial structural elements under continual fracture condition - Bazhenov, V. A.; Gulyar, O. I.; Pyskunov, S. O. (КНУБА, 2014)
The techniques of modeling of continual fracture process for space circular and prismatic bodies under prolonged load condition and some results of determining of the estimated lifetime (up to local loss of material bearing capacity) and the residual (additional) lifetime (time of continual fracture zone growth) is presented in this paper. The Kachanov-Rabotnov’s scalar damage parameter to describe the continual fracture of the material and the semianalytic finite element method (SFEM) as numerical method of boudary problem solution is used. It‘s shown, that the value of residual lifetime could be differ significantly for different loading condition and object configuration.
Keywords: creep; cyclic loading; damage; continual fracture; lifetime; spatial problem; semianalytic finite element method (SFEM); the department building mechanics; 539.3:539.4